Electrochemical and Thermal Stress of LiNi0.8Co0.15Al0.05O2 Electrodes: Evolution of Aluminum Surface Environments. (25th October 2017) - Lebens-Higgins, Zachary; Faenza, Nicholas; Mukherjee, Pinaki; Sallis, Shawn; Badway, Fadwa; Pereira, Nathalie; Schlueter, Christoph; Lee, Tien-Lin; Cosandey, Frederic; Amatucci, Glenn; Piper, Louis F.J.
Abstract : For layered oxide cathodes, aluminum doping has widely been shown to improve performance, particularly at high degrees of delithiation. While this has led to increased interest in Al-doped systems, including LiNi0.8 Co0.15 Al0.05 O2 (NCA), the aluminum surface environment has not been thoroughly investigated. Using hard x-ray photoelectron spectroscopy measurements of the Al 1s core region for NCA electrodes, we examined the evolution of the surface aluminum environment under electrochemical and thermal stress. By correlating the aluminum environment to transition metal reduction and electrolyte decomposition, we provide further insight into the cathode-electrolyte interface layer. A remarkable finding is that Al-O coatings in LiPF6 electrolyte mimic the evolution observed for the aluminum surface environment in doped layered oxides.